Electricity on Paper - Kolomiets, S.; Andreev, A.; Andreeva, O.; Minakova, K. A. (Serednyak T. K., 2019)
The paper proposes a practical cycle of classes on electricity at school. The main goal of these classes is to form students' interest in physics and electronics, as well as acquaint them with the basics of building electrical circuits and their main components.
Keywords: STEM education; entertaining circuitry; practical electricity classes; schoolchildren